Rapid biosynthesis of silver nanoparticles using culture supernatant of bacteria with microwave irradiation - Saifuddin N.; Wong C.W.; Yasumira A.A.N. (WWW Publications PTE India, 2023)
The development of rapid and reliable processes for the synthesis of nanosized materials is of great importance in the field of nanotechnology. Synthesis of silver nanoparticles using microorganism have been reported, but the process is rather slow. In this paper, we describe a novel combinatorial synthesis approach which is rapid, simple and "green" for the synthesis of metallic nanostructures of noble metals such as silver (Ag), by using a combination of culture supernatanant of Bacillus subtilis and microwave (MW) irradiation in water in absence of a surfactant or soft template. It was found that exposure of culture supernatanant of Bacillus subtilis and microwave irradiation to silver ion lead to the formation of silver nanoparticles. The silver nanoparticles were in the range of 5-60 nm in dimension. The nanoparticles were examined using UV-Visible Spectroscopy, and Transmission Electron Microscopy (TEM) analyses. The formation of nanoparticles by this method is extremely rapid, requires no toxic chemicals and the nanoparticles are stable for several months. The main conclusion is that the bio-reduction method to produce nanoparticles is a good alternative to the electrochemical methods.